A rare case: Congenital Megalourethra in prune belly syndrome - Selvi, Ismail; Baydilli, Numan; Akınsal, Emre Can (Archives of Case Reports, 2018)
Introduction: Prune Belly syndrome is a disease characterized by abdominal muscle defect, bilateral cryptorchidsim and urinary system anomalies (reflux megaureter, hydronephrosis, etc.). Pulmonary, cardiac, and gastrointestinal anomalies may also be present. Management of these rare cases is very important. In this case, the clinical course of a patient with Prune Belly syndrome with megaurethra is presented. Case: The patient from the first gestation and parturition with birth weight of 2500 g and 38 weeks was hospitalized because of the bilateral hydronephrosis. His physical examination revealed undescended testicles and a large penis. The abdominal muscles were not very atrophic. The size of the kidney was small, bilateral hydroureteronephrosis and wide posterior urethra on the ultrasound. Renal function tests were progressively disturbed and the patient underwent cystourethroscopy for diagnostic purposes in terms of posterior urethral valve. A large diverticulum was found in anterior urethra. Prune Belly Syndrome was thought because the orifices were in appearance of reflux. The vesicostomy was applied. After vesicostomy the renal function tests got better but he was hospitalized due to urosepsis two times. In cystoscopic examination, the diverticulum in the urethra was filled with urine and the drainage was very slow. Phimosis was opened with dorsal slit technique. Cutaneous urethrostomy was proximal to the anterior diverticulum. Conclusion: Prune Belly syndrome should be considered in patients with megaurethra and postrenal or renal insufficiency although there are no obvious clinical findings. In Prune Belly cases, via a large penis with obstruction signs, anterior urethral diverticulum should be considered.